Heart rate variability and quality of life in dogs with mitral valve disease treated with metoprolol - Beluque, Tamyris [UNESP]; Camacho, Aparecido Antonio [UNESP]; Ampuero, Roberto Navarrete [UNESP]; Braz, Jaislane Bastos [UNESP]; Kirnew, Murillo Daparé [UNESP]; Canola, Raphaela Arantes Marques [UNESP]; Carvalho, Elizabeth [UNESP]; Sousa, Marlos Gonçalves (Revista Brasileira de Medicina Veterinaria, 2021)
Mitral valve disease (MVD) is a progressive disease that can reduce cardiac output. Activation of the sympathetic autonomic nervous system is one of the body’s first responses in order to maintain cardiac output, but may have deleterious effects on the cardiovascular system. This study investigated the effect of metoprolol on heart rate variability and quality of life in dogs with severe MVD (stage C, according to the guidelines of the American College of Veterinary Internal Medicine). Eight dogs between nine and thirteen years of age were enrolled and screening tests such as complete blood count, serum biochemistry profile, systolic blood pressure, thoracic radiographs, electrocardiogram, echocardiogram and long-term electrocardiography (24 hours) were performed. The patients were treated with enalapril, furosemide, spironolactone, and pimobendan until considered clinically stable, and metoprolol was then added to the therapy. One month later, all animals were re-assessed. Owners responded to a questionnaire about their dog’s quality of life before and after beta-blocker therapy. The value for pNN50 (percentage difference between adjacent N-N intervals more than 50 ms) was significantly higher (P=0.039) after treatment with metoprolol, indicating higher heart rate variability as indicated by the increased parasympathetic component. Furthermore, quality of life was improved in 30% of patients after metoprolol was initiated. The results suggest that treatment with beta-blockers in dogs with stage C MVD may yield additional benefits in comparison to standard CHF treatment.
Keywords: Autonomic nervous system; Beta-blockers; Holter; PNN50